A prospective observational study of branching pattern of middle hepatic vein on contrast enhanced computed tomography - Rai, Arvind; Khan, Avais Ahmed (International Surgery Journal, 2020)
Background: The main purpose of pre-operative imaging in liver transplantation is to expose the arterial and venous vascular map. Prior to transplantation it is necessary to image the vascular structures property due to complex nature of liver vascular anatomy and its frequent variations. CT is a useful method not only in the determination of hepatic arterial anatomy, hepatic venous anatomy, accessory hepatic veins and portal veins variations. Methods: This was a prospective observational study performed at the department of surgery, Gandhi Medical College Bhopal and study of CECT was carried out in the department of radiodiagnosis with approval from college ethical committee on 100 patients during a period of 2 years from 2017 to 2019. Results: In study of 100 cases were studied. The study mainly done on the MHV mainly its length, width draining segments of liver by MHV and accessory hepatic veins. In overall cases maximum cases had drainage from segment IVb, V and segment VIII. The segment 5 accessory vein is the most common single accessory vein found in the study. Conclusions: Many parameters of MHV have studied in the study and understanding of these parameters is undoubtedly important for operating surgeon its anatomical draining patterns, draining liver segments and has got the presence of the various accessory veins in the liver. Recognition of these accessory hepatic veins is important because some of these accessory veins may become useful in segmental liver transplantation.